From the Gut to the Brain and Back: Therapeutic Approaches for the Treatment of Network Dysfunction in Parkinson's Disease - Paolone, Giovanna (Frontiers in Neurology, 2020)
Parkinson's disease (PD) is a complex, multisystem, progressive, degenerative disorder characterized by severe, debilitating motor dysfunction, cognitive impairments, and mood disorders. Although preclinical research has traditionally focused on the motor deficits resulting from the loss of nigrostriatal dopaminergic neurons, up to two thirds of PD patients present separate and distinct behavioral changes. Loss of basal forebrain cholinergic neurons occurs as early as the loss of dopaminergic cells and contributes to the cognitive decline in PD. In addition, attentional deficits can limit posture control and movement efficacy caused by dopaminergic cell loss. Complicating the picture further is intracellular α-synuclein accumulation beginning in the enteric nervous system and diffusing to the substantia nigra through the dorsal motor neurons of the vagus nerve. It seems that α-synuclein's role is that of mediating dopamine synthesis, storage, and release, and its function has not been completely understood. Treating a complex, multistage network disorder, such as PD, likely requires a multipronged approach. Here, we describe a few approaches that could be used alone or perhaps in combination to achieve a greater mosaic of behavioral benefit. These include (1) using encapsulated, genetically modified cells as delivery vehicles for administering neuroprotective trophic factors, such as GDNF, in a direct and sustained means to the brain; (2) immunotherapeutic interventions, such as vaccination or the use of monoclonal antibodies against aggregated, pathological α-synuclein; (3) the continuous infusion of levodopa-carbidopa through an intestinal gel pad to attenuate the loss of dopaminergic function and manage the motor and non-motor complications in PD patients; and (4) specific rehabilitation treatment programs for drug-refractory motor complications.